Qualitative and quantitative analysis of PMN/T-cell interactions by InFlow and super-resolution microscopy - Balta, Emre; Stopp, Julian; Castelletti, Laura; Kirchgessner, Henning; Samstag, Yvonne; Wabnitz, Guido H. (Methods, 2017)
Neutrophils or polymorphonuclear cells (PMN) eliminate bacteria via phagocytosis and/or NETosis. Apart from these conventional roles, PMN also have immune-regulatory functions. They can transdifferentiate and upregulate MHCII as well as ligands for costimulatory receptors which enables them to behave as antigen presenting cells (APC). The initial step for activating T-cells is the formation of an immune synapse between T-cells and antigen-presenting cells. However, the immune synapse that develops at the PMN/T-cell contact zone is as yet hardly investigated due to the non-availability of methods for analysis of large number of PMN interactions. In order to overcome these obstacles, we introduce here a workflow to analyse the immune synapse of primary human PMN and T-cells using multispectral imaging flow cytometry (InFlow microscopy) and super-resolution microscopy. For that purpose, we used CD3 and CD66b as the lineage markers for T-cells and PMN, respectively. Thereafter, we applied and critically discussed various “masks” for identification of T-cell PMN interactions. Using this approach, we found that a small fraction of transdifferentiated PMN (CD66b+CD86high) formed stable PMN/T-cell conjugates. Interestingly, while both CD3 and CD66b accumulation in the immune synapse was dependent on the maturation state of the PMN, only CD3 accumulation was greatly enhanced by the presence of superantigen. The actin cytoskeleton was weakly rearranged at the PMN side on the immune synapse upon contact with a T-cell in the presence of superantigen. A more detailed analysis using super-resolution microscopy (structured-illumination microscopy, SIM) confirmed this finding. Together, we present an InFlow microscopy based approach for the large scale analysis of PMN/T-cell interactions and - combined with SIM - a possibility for an in-depth analysis of protein translocation at the site of interactions.